Geographical Learning through Traditional Practices: The Case of Assuro Maca in Labakkang, Pangkep Indonesia - Syamsunardi; Syarif, Erman; Maddatuang; Zhiddiq, Sulaiman; Achmad, St. Aqilah Raihanah (CV Bumi Spasial, 2024)
This research aims to determine the process of the assuro maca tradition of the Labakkang sub-district community, Pangkep district. The process in this case includes the history of the beginning of the assuro maca tradition, the development of the Assuro maca tradition and the continuation of the Assuro maca tradition. This type of research is qualitative descriptive research. Data collection methods are through interviews, participatory observation and documentation in obtaining primary data to be used as research results which are supported by secondary data sourced from studies of scientific literature. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The research results show that the beginning of the assuro maca tradition began when Islam entered the archipelago. The development of the assuro maca tradition, in the past, its implementation was carried out in a large house which was usually called Arajang, but as time progressed, people now had private homes that were capable of doing so, so the implementation of the assuro maca tradition was carried out in their own homes. The potential for the assuro maca tradition is very large due to the values of brotherhood and togetherness inherent in this tradition.